2011
DOI: 10.1021/ef200883r
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Dispersion of Distributions as a Probe of Aggregation in Crude Oils

Abstract: We present a new technique-nuclear magnetic resonance dispersion of distributions (NMRDD)-and we demonstrate that it is a particularly sensitive probe of aggregation in asphaltene-rich crude oils. The technique is based on the measurement of the NMR relaxation distributions at different magnetic fields, i.e., at different proton Larmor frequencies. Because the NMR relaxation rates are controlled by molecular fluctuations at the Larmor frequency, these measurements probe the presence of aggregates that tumble a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 20 publications
6
34
0
Order By: Relevance
“…This difference in the T 1 /T 2 ratio persists in a solution of chloroform-d and 3 vol% of the tracer molecule (benzene-f 6 and octane-f 18 ) containing 10 wt% asphaltenes [13], extracted from the previous investigated asphaltenic oil. Furthermore, a strong dispersion of T 1 at Larmor frequencies between 10 6 Hz and 10 8 Hz was observed for the aromatic molecules in the asphaltenic oil, which is in accordance with the T 1 dispersion of the maltene mixtures present in crude oils containing asphaltenes [14][15][16]. In contrast, a significantly weaker dispersion is observed for octane-f 18 in the asphaltenic oil as well as for the aromatic molecules in the asphaltene-free oil [11].…”
Section: Introductionsupporting
confidence: 80%
“…This difference in the T 1 /T 2 ratio persists in a solution of chloroform-d and 3 vol% of the tracer molecule (benzene-f 6 and octane-f 18 ) containing 10 wt% asphaltenes [13], extracted from the previous investigated asphaltenic oil. Furthermore, a strong dispersion of T 1 at Larmor frequencies between 10 6 Hz and 10 8 Hz was observed for the aromatic molecules in the asphaltenic oil, which is in accordance with the T 1 dispersion of the maltene mixtures present in crude oils containing asphaltenes [14][15][16]. In contrast, a significantly weaker dispersion is observed for octane-f 18 in the asphaltenic oil as well as for the aromatic molecules in the asphaltene-free oil [11].…”
Section: Introductionsupporting
confidence: 80%
“…An attempt to fit the data by the formalism detailed in [22] was unsuccessful. A comparably strong power-law dependence in crude oils has been reported in [8,24] and was interpreted by a model involving the tumbling of finite-sized asphaltene aggregates. However, qualitatively comparable results were found for a number of bitumen samples, one of which is shown in Fig.…”
Section: Resultsmentioning
confidence: 67%
“…Recently, the maltene content trapped in precipitated asphaltene has been described [7]. Even in the solution state, asphaltene aggregates can be considered as porous structures and the molecular dynamics of maltenes in confined spaces will be affected similarly to conventional, solid porous media [8], with maltenes being in exchange between the confinement and the free phase.…”
Section: Introductionmentioning
confidence: 99%
“…Zielinski and Hürlimann demonstrated that T 1 relaxation time profiles determined on crude oils can provide information on the tumbling rates of asphaltene aggregates in heavy oils, which is considered to be a useful precursor to flocculation [97]. The new approach, known as NMR dispersion of distributions (NMRDD) involves measuring the T 1 relaxation profiles as a function of the Larmor frequency of the protons.…”
Section: Accepted Manuscriptmentioning
confidence: 99%